Changes in The Biological and Nutritional Value of Halva Enriched with Sesame and Flax Seeds - Salikhanova Dilnoza; Nazirova Rahnamokhon; Munisa Mamajonova; Dilafruz Sagdullaeva (Emerging Frontiers Library for The American Journal of Applied Sciences, 2026)
This work studies the possibilities of increasing the nutritional and biological value of traditional halva by enriching it with sesame and flax seeds. According to the results of the study, the introduction of these additives increased the content of protein, fat, dietary fiber and minerals in the product, and to a certain extent reduced the share of carbohydrates. At the same time, the composition of fatty acids improved qualitatively, and in particular, the content of omega-3 fatty acids increased significantly. The study also revealed that the antioxidant properties of the product increased as a result of the addition of sesame and flax seeds. The increase in phenolic compounds and total antioxidant activity indicators confirms the increased contribution of functional components. As a result, such halva is considered not only a high energy source, but also a functional food product that meets the requirements of healthy nutrition.